Relationship Between Chronic Obstructive Pulmonary Disease and Osteoporosis: A Scoping Review - Ana Penedones; Diogo Mendes; Carlos Alves; Augusto Filipe; Tânia Oliveira; Francisco Batel-Marques (COPD, 2024)
Introduction Potential associations between Chronic Obstructive Pulmonary Disease (COPD) and osteoporosis have been studied, but areas of uncertainty remain.Objective This scoping review aimed to identify the published evidence on the epidemiological relationships between COPD and osteoporosis.Methods Experimental and observational evidence evaluating relationships between COPD and osteoporosis on epidemiology, clinical manifestations, risk factors (RFs), therapeutic management and quality of life (QoL) was searched on PubMed and Embase (until May 2023). The studies were categorized according to their objectives and characteristics. Data were analyzed using descriptive statistics.Results Ninety-nine studies were selected, namely 33 (33%) reporting epidemiologic measures, 11 (11%) clinical manifestations, 74 (75%) RFs (45 ones, of which body mass index [BMI; n = 22 studies], corticosteroids’ use [n = 20], and COPD severity [n = 15] were the most studied), 7 (7%) therapeutic management, and 3 (3%) QoL. Twenty-seven (27.6%) studies evaluated ≥2 domains. Most studies followed a cross-sectional design (n = 37; 37.4%). Eighty-nine studies (90%) assessed patients with COPD at baseline and studied its relationship with osteoporosis.Conclusion There are well-established features linking COPD and osteoporosis, including shared RFs, such as smoking, elderly, physical inactivity, or low BMI. Others deserve clarification, including the impact of COPD severity, or the use of inhaled corticosteroids on the incidence of osteoporosis and fractures, as well as the value of performing routine imaging tests, or prescribing anti-resorptive medications in COPD to prevent osteoporotic-related outcomes. QoL studies are also lacking. Investigating such issues is needed to propose clinical guidelines for managing osteoporosis in patients with COPD.